Recent developments in the synthesis of superabsorbent polymer from natural food sources: A review - Yamuna , V.; Kandhavadivu, P. (The Scientific Temper, 2023)
Superabsorbent polymer is a water absorbing polymer which absorbs and holds large amount of water where it is widely used in agriculture and in incontinent pads. In earlier days, superabsorbent polymer was synthesized purely from synthetic materials which are now being replaced with the combination of natural materials due to the awareness of eco friendliness and biodegradability. Many research works have been carried out in the preparation of natural based SAPs. Hence this review focus on the general process of SAP preparation, mechanism and the types of natural products which is used in food products in recent days for the synthesis of SAP. Test methods to be carried out for SAP and the future scope of SAP preparation without any synthetic products have to be analyzed in order to meet the challenges of environment for biodegradability